2010
DOI: 10.1111/j.1460-9568.2010.07081.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ release‐dependent inactivation of Ca2+ currents in thalamocortical relay neurons

Abstract: Neuronal Ca(2+) channels are rapidly inactivated by a mechanism that is termed Ca(2+)-dependent inactivation (CDI). In this study we investigated the influence of intracellular Ca(2+) release on CDI of high-voltage-activated Ca(2+) channels in rat thalamocortical relay neurons by combining voltage-clamp, Ca(2+) imaging and immunological techniques. Double-pulse protocols revealed CDI, which depended on the length of the conditioning pulses. Caffeine caused a concentration-dependent increase in CDI that was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…However, the net level of [Ca 2+ ] i increases in ventrobasal TC relay neurons in humans in vivo is unknown and will also depend on whether lidocaine affects other regulatory mechanisms of Ca 2+ homeostasis, such as Ca 2+ -induced Ca 2+ release, Ca 2+ -dependent inactivation, and functioning of the Na + -Ca 2+ exchanger. 35,[49][50][51] For example, Xu et al 22 reported that lidocaine inhibits KCl-and carbachol-evoked intracellular Ca 2+ transients in a concentration range similar to that in our study (0.1-2.3 mM), albeit in a neuronal cell culture. Clearly, further research, including studies using Figure 5.…”
Section: Discussionsupporting
confidence: 74%
“…However, the net level of [Ca 2+ ] i increases in ventrobasal TC relay neurons in humans in vivo is unknown and will also depend on whether lidocaine affects other regulatory mechanisms of Ca 2+ homeostasis, such as Ca 2+ -induced Ca 2+ release, Ca 2+ -dependent inactivation, and functioning of the Na + -Ca 2+ exchanger. 35,[49][50][51] For example, Xu et al 22 reported that lidocaine inhibits KCl-and carbachol-evoked intracellular Ca 2+ transients in a concentration range similar to that in our study (0.1-2.3 mM), albeit in a neuronal cell culture. Clearly, further research, including studies using Figure 5.…”
Section: Discussionsupporting
confidence: 74%
“…To investigate whether the [Ca 21 ] i transients induced by (-)-Cv resulted from calcium release of intracellular stores, DRG neurons were bathed in calcium-free KRH. A caffeine (3 mM) and thapsigargin (1 lM) solution was used to induce internal calcium release (17,18). While (-)-Cv (1 mM) in the absence of extracellular calcium was not able to cause any fluorescence change in these conditions, [Ca 21 ] i transients were observed following application of caffeine plus thapsigargin solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the inhibition may be similar to the inhibition by caffeine of L-type VGCCs in thalamocortical relay neurons [54]. Rankovic et al [54] suggested that, as in cardiac myocytes, the coupling between L-type VGCCs and RyRs in thalamocortical neurons occurs in a confined area where a cluster of RyRs is juxtaposed with a group of L-type VGCCs, forming a ‘Ca 2+ release unit’.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition may be similar to the inhibition by caffeine of L-type VGCCs in thalamocortical relay neurons [54]. Rankovic et al [54] suggested that, as in cardiac myocytes, the coupling between L-type VGCCs and RyRs in thalamocortical neurons occurs in a confined area where a cluster of RyRs is juxtaposed with a group of L-type VGCCs, forming a ‘Ca 2+ release unit’. They further suggested that the interaction between Ca 2+ release units is enhanced by caffeine, which increases the sensitivity of RyRs for Ca 2+ and evokes the spread of Ca 2+ -induced Ca 2+ release across the ER (possibly filling up a shell of Ca 2+ ions beneath the plasma membrane and allowing Ca 2+ cooperativity), or by neurotransmitter-stimulated recruitment of L-type VGCCs and RyRs.…”
Section: Discussionmentioning
confidence: 99%